THE ANALYSIS ON BACKGROUND, ORGANIZING PRINCIPLE, AND TYPE OF SYLLABUS ON ENGLISH COURSEBOOK ENGLISH IN FOCUS - Imam Munandar (Asosiasi Dosen Perguruan Tinggi Islam, 2020)
This research tries to look closely at the background, organizing principle, and how the English in Focus coursebook is designed. To figure out the answer, the research employs a qualitative study with a descriptive approach. The book itself is analyzed by using three parameters set by Canale and Swain, namely 1. The background, 2.Organizing principle, and 3.Type of the syllabus. The research has found that the book is designed to be used in a target-removed context in the EFL context. Furthermore, the book follows the functional/notional syllabus. The conceptualization of language is designed to follow communicative functions, incorporating Canale and Swain's language model involving linguistic, discourse socio-cultural, and strategic components. Following that, the book integrates other syllabus strands. The functional approach is shown by different language functions presented to students, while the discourse syllabus is realized in the speech acts involving politeness and formal and informal language. The structural syllabus is indicated by the grammar items to be learned by students inductively. However, some issues should be addressed in the book. The strategic competence that underlies the syllabus is limitedly realized in the classroom activities. In this case, the books should consider the tasks that enable students to develop their skills in avoiding communication breakdowns such as turn-taking and repair.